A case of peritonitis caused by Roseomonas gilardii in a patient undergoing continuous ambulatory peritoneal dialysis. - Sandoe, J A (1997)
A case of peritonitis caused by Roseomonas gilardii in a patient receiving continuous ambulatory peritoneal dialysis is presented. The patient's domestic water supply was implicated as the probable source of infection. This is the first report of R. gilardii causing such an infection.